Interrelation between subjective assessment of mental state and perception of family relations by relatives caring for patients with addiction - A. I. Nechaeva; A. M. Shishkova; D. I. Gromyko; V. V. Bocharov; R. D. Ilyuk (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The addictive disorder often becomes a difficult experience for the all family. Studying the factors influencing the level of psychological distress of addicted patients’ relatives is necessary to create an effective system of psychological assistance for them.Purpose: to reveal the interrelations between the subjective assessment of the mental state and the perception of family relationships among relatives of patients with pathological gambling (PG) and relatives of patients with stimulant use disorder (SUD).Materials and methods. In a cross-sectional study 100 and 41 patients’ relatives were included in the PG and SUD groups respectively. The Symptom Checklist-90-Revised (SCL-90-R) and the Family Environment Scale (FES) was used as an assessment tools. Socio-demographic and clinical data were also collected.Results. The analysis of interrelations between the severity of psychopathological symptoms and the perception of family relationships in the studied groups determined both general and specific correlations. In both groups there are multiple negative correlations between the majority of SCL-90-R scales and the “Cohesion” scale (FES). The specific interrelations included, for example, multidirectional correlations between the “Expressiveness” scale (FES) and psychopathological symptoms scales of the SCL-90-R. Increased expressiveness in the PG group was associated with less severity of psychopathological symptoms and level of distress, and, on the contrary, a greater severity of psychological distress in respondents of the SUD group. Analysis of the correlations in PG compared to SUD showed greater predictability of the connections between psychopathological symptoms and perception of family relationships in the PG group. Thus, the indicators of psychopathological symptoms and psychological distress are negatively associated with parameters reflecting the perception of family cohesion, trust in intrafamily relations, social activity and family organization and, at the same time, have positive interrelations with the indicator of conflict in family relationships.Conclusion. The perception of the family cohesion function as the intrapsychic protection that facilitate the relatives’ adaptation in the emerging life situation, regardless of the form of patients’ addiction.